A multi-national peer support intervention: the UPSIDES pilot phase. (2nd January 2022) - Nixdorf, Rebecca; Nugent, Lena; Aslam, Rabeea'h; Barber, Sarah; Charles, Ashleigh; Gai Meir, Lion; Grayzman, Alina; Hiltensperger, Ramona; Kalha, Jasmine; Korde, Palak; Mtei, Rachel; Niwemuhwezi, Jackie; et al.
ABSTRACT: Objective: Using Peer Support in Developing Empowering Mental Health Services (UPSIDES) is evaluating implementation of a peer support worker (PSW) intervention at six recruiting sites (Germany, India, Israel, Tanzania, and Uganda) (ISRCTN26008944). The aim of this study is to evaluate the pre-trial pilot phase. Method: The initial training to prepare individuals for the PSW role and the implementation of the peer support (PS) intervention was evaluated using a multi-method design comprising six focus groups (FG; n  = 22) and questionnaires capturing the perspectives of service users, PSWs, peer trainers, and mental health staff members ( n  = 21). Results: Findings were organised across eleven key implementation themes: organisational culture, PSW training, PSW role definition, staff willingness and ability to work with PSWs, resource availability, financial arrangements, support for PSW well-being, PSW access to a peer network, acceptance, preparation, and other challenges. Discussion: The following recommendations are made, based on this pilot phase: the PS training should train on practical skills using role-playing exercises; PSWs should work in teams, including role reflection with colleagues (intervision) or with a highly experienced coach (supervision); necessary resources and tools for networking should be provided; and continuous awareness-raising about PS is needed.